ANALYSIS OF LANDSLIDE DISASTER IN KEDUNGSARI VILLAGE, GEBOG SUBDISTRICT, KUDUS DISTRICT - winda, Winda Irmalia Sari; Rafi Hidayat; Dany Miftah M. Nur (International Journal of Multidisciplinary Reseach, 2025)
Landslides that occurred in Kedungsari Village, Gebog Subdistrict, Kudus Regency, in 2022 were caused by a combination of natural factors and unstable environmental conditions, but did not cause casualties. The purpose of this study was to determine the level of knowledge and the role of the community in disaster management. This research used a qualitative descriptive method. The data collection technique used was interviews to get a further picture of the landslide disaster that had occurred in the place and the role of the local community in mitigation and recovery efforts. The results showed that there were no fatalities or injuries in this incident, but this incident can cause fear, potential psychological trauma, and concern to local residents. Mitigation efforts and community involvement are essential to reduce risk and restore post-disaster conditions. This research can also be a source of accurate information for government agencies and private institutions.